Guided Imagery Relaxation for Acute Pain in Pre-Operative Paralitic Ileus Patient: A Case Study - Nur Rofi'ah, Siti; Hakam, Mulia; Murtaqib; Mustakim (Al-Hijrah Indonesia, 2023)
Patients with paralytic ileus generally have complaints of abdominal pain of uncertain duration. The pain that appears can get worse with anxiety about something being experienced, such as a surgical action plan. Feelings of anxiety can be a stressor and cause nursing problems in the form of anxiety. Guided imagery therapy is known to be a non-pharmacological therapy in dealing with pain and feelings of anxiety in preoperative patients. This study aims to analyze the administration of guided imagery relaxation therapy to the problem of acute preoperative pain in patients with paralytic ileus. The research method used in this study was a descriptive case study. The research was conducted for three days on one patient with preoperative paralytic ileus in the Mawar Room at RSD dr. Soebandi Jember. Guided imagery therapy is carried out twice daily for 20-30 minutes. The results obtained from this study were that after pain management was carried out with guided imagery therapy, the patient's pain level decreased from the NRS 6 scale to the NRS 5 scale, respiratory frequency 20x/minute, SpO2 96%, blood pressure 130/100 mm Hg, pulse rate 101x/minute. Reducing the pain scale results indicate that guided imagery therapy can be applied to treat pain and anxiety in preoperative patients to improve their condition. respiratory frequency 20x/minute, SpO2 96%, blood pressure 130/100 mmHg, pulse rate 101x/minute. Reducing the pain scale results indicate that guided imagery therapy can be applied to treat pain and anxiety in preoperative patients to improve their condition. respiratory frequency 20x/minute, SpO2 96%, blood pressure 130/100 mmHg, pulse rate 101x/minute. Reducing the pain scale results indicate that guided imagery therapy can be applied to treat pain and anxiety in preoperative patients to improve their condition.